Freedom of Expression and Hate Speech: When Values Collide in Divided Societies - Bertus de Villiers (Constitutional Review, 2022)
One of the thorniest issues in law, especially concerning the boundaries of what is reasonable and proportionate, is the distinction between freedom of expression and hate speech. Striking a balance between freedom of expression and hate speech is, however, not a mere exercise in theory; it goes to the core of respect of individual rights and freedoms. To one person, uttering speech pursuant to the right to free expression is essential for a free and open democratic society; whereas another person, offended by what they perceive as hatred, can experience such speech as an attack on their identity and self-worth, causing harm, fear and anxiety that deny their individual rights to equality, identity and dignity. This paper gives a brief overview of jurisprudential developments in international law concerning speech that may fall within the category of hate speech, whereafter two prominent South African judgments by the Equality Court are discussed. Those two judgments highlight the complexities in determining when speech can be regarded as hate speech; what test is applied to ascertain whether speech constitutes hate speech; what evidence is required for a finding to be made; and the effect of a declaratory order. The two judgments discussed, the Nelson Mandela Trust and Ors v. AfriForum and Ors (Old Flag case 2019) and the AfriForum and Economic Freedom Fighters and Ors (Kill the Boer Case 2022), attempted to determine the line that separates freedom of expression from hate speech. The judgments, perhaps not unexpectedly, have given rise to more questions than answers. The inconsistency in comparative jurisprudence reaffirms that the labelling of speech as hate speech should be reserved for the most extreme forms of speech; it should be proportionate to the speech, including who expressed it, where and when; and any declaration should only be directed at the specific incident and not restrict speech in general.